Development of a hardware in the loop rig for an autonomous underwater glider from a product development standpoint - Persson, Oskar (My University, 2026)
This thesis presents the design and implementation of hardware in the loop (HIL) rig developed for the autonomous underwater glider (AUG) SeaGul. The rig simulates real dives by reading and responding to the actual hardware output of SeaGul with the use of load cells. During these simulated dives load cell data are sent to the simulation that calculates depth, distance, amount of water displaced, centre of gravity (CoG), pitch, and roll. Data calculated during the simulated dives are compared with results from real world dives. By analysing pitch and depth readings along with estimated timing between samples, the system approximates the glider’s speed and distance covered in each dive phase. Providing a simplified simulation that can also get hardware responses in specific circumstances and edge cases. In addition, this work investigates the potential of HIL rigs as effective tools for the development and testing of AUG. The results show that the HIL rig can find the CoG which is useful when ballasting SeaGul. It can also replicate core dive behaviours, such as response at depth, surfacing, and orientation changes. Furthermore, can the HIL rig consistently provide approximate estimations of dive speed, acceleration, pitch, roll, depth, and distance travelled but with limited precision. This highlights both the utility of the system and the need for improved simulation. Despite sensitivity to disturbances and limitations due to incomplete real dive data, the HIL rig functions as intended, and all hardware components operate reliably. This demonstrates that the HIL rig is a valuable development and testing platform for SeaGul and potentially other AUG’s. Supporting key behaviour insights, CoG calibration, and the ability to evaluate hardware responses under controlled edge case scenarios.
Keywords: Hardware in the loop (HIL); Autonomous underwater glider (AUG); System validation; Product development; SeaGul